TRANSITION TO RENEWABLE ENERGY SOURCES IN UZBEKISTAN - Shoh-Jaxon Hamdamov (Insurance market of Uzbekistan, 2024)
This scholarly article investigates the shift towards renewable energy sources within Uzbekistan, accentuating the critical role of accessible and sustainable energy in fostering sustainable development, economic advancement, and ecological preservation. Notwithstanding the nation's substantial dependence on fossil fuels, particularly on natural gas, Uzbekistan harbors considerable prospects for renewable energy, especially in the domains of solar, wind, and hydropower. The article delineates principal obstacles encountered during this transition, including infrastructural deficiencies, financial limitations, and regulatory impediments. It advocates for strategic interventions, such as investment in renewable energy infrastructure, implementation of policy reforms, and establishment of public-private partnerships, to enable a successful transition towards a sustainable energy paradigm. By capitalizing on its renewable resources, Uzbekistan can attain energy security, diminish greenhouse gas emissions, and enhance economic resilience.